Influence of stone load on the outcome of same-session flexible ureteroscopy for bilateral upper urinary tract stones: a multicenter retrospective study - Tu, Wei-Chao; Zhang, Xin-Le; Wang, Jun; Huang, Bao-Xing; Zhang, Ding-Guo; Wang, Da-Wei (Frontiers in Medicine, 2023)
Purpose This study aimed to evaluate the efficacy and safety of same-session flexible ureteroscopy (fURS) for the treatment of bilateral upper urinary tract stones and to examine the influence of stone load on the outcome of same-session fURS, stratifying by total diameter of stones (TDS) ≤30 mm vs. >30 mm. Patients and methods We retrospectively reviewed all cases of same-session fURS performed for bilateral upper urinary tract stones at four institutions between January 2017 and September 2020. All patients were divided into two groups based on TDS, ≤30 mm and >30 mm. Data on patient demographics, stone characteristics, surgical results, and complications were collected and analyzed for differences between the two groups. Stone-free rate (SFR) was defined as patients endoscopically stone-free or with radiological fragments <2 mm of each renal unit. Results A total of 121 patients with bilateral upper urinary tract stones underwent same-session fURS, consisting of 73 patients in the TDS ≤ 30 mm group and 48 patients in the TDS > 30 mm group. The mean bilateral stone size was 28.2 ± 12.2 mm (range: 9.1–38.4 mm), with a mean operating time of 97.1 ± 39.6 min (range: 19–220 min). The SFR was 54.5% after the first fURS, and SFR increased to 97.5% after re-fURS for residual stones. The operation time for the TDS > 30 mm group was longer than that of the TDS ≤ 30 mm group (85.1 ± 36.5 vs. 115.4 ± 37.4 min, p < 0.001). The SFR after the first fURS was significantly lower in the TDS > 30 mm group than in the TDS ≤ 30 mm group (25.0% vs. 73.9%, p < 0.001). Although there was no statistically significant difference in overall SFR between the two groups (93.7% vs. 100%, p = 0.060), the rate of re-fURS for residual stones was higher in the TDS > 30 mm group than in the TDS ≤ 30 mm group (75% vs. 26%, p < 0.001). There were no significant differences in length of hospital stay (LOS) (2.2 ± 0.7 vs. 2.3 ± 1.0, p = 0.329) or complication rate (10.9% vs. 14.6%, p = 0.582) between the two groups. Conclusion The results suggested that same-session fURS can be effectively performed with a low complication rate. A higher SFR after the first fURS can be achieved in the case of bilateral upper urinary tract stones with TDS ≤ 30 mm, and priority should be given to same-session fURS.